Workshop Pengembangan Bahan Ajar Terintegrasi Object 3D dan Augmented Reality Bagi Guru SDN 31 Cakranegara - Erfan, M.Pd, Muhammad; Dewi, Nurul Kemala; Istiningsih, Siti; Wahyuningsih, Baiq Yuni; Aulia, Aulia; Aulia, Anisa Rizki (Abdimas Mandalika, 2025)
This community service activity aims to introduce one of the LMS platforms that can integrate 3D Objects and Augmented Reality through each teacher's smartphone device. Assemblr Edu, one of the easy-to-use learning platforms, and the existing materials can also be integrated with 3D Objects and Augmented Reality, is not widely known by educators, especially at SDN 31 Cakranegara. The training activity was carried out on Monday, September 2, 2024, which was attended by the principal of SDN 31 Cakranegara and the teachers. The training materials include an introduction to the Assemblr Edu platform, the Assemblr Edu Android Application, registering an account on Assemblr Edu, how to log in to an account on Assemblr Edu, adding and managing students on the Assemblr Edu Platform, and adding various 3D objects and integrating them with Augmented Reality through scannable markers. The training activity was categorized as successful because several teachers have created classes on the Assemblr Edu platform and can integrate 3D Objects and teaching materials integrated with Augmented Reality in classes managed by teachers at SDN 31 Cakranegara.